Implementasi Program Labbaik dalam meningkatkan Mutu Pembelajaran Kitab Kuning Santri - Robi’atul Adhawiyah (Fakultas Agama Islam Universitas Billfath, 2022)
The LABBAIK Program (Institute for Quran and Book Reading Guidance) at PP Mambaus Sholihin Suci Gresik is a mandatory program for students enrolled at MA Mambaus Sholihin and UNKAFA university students. This program consists of two activities: the first focuses on guiding fluency in reading the Quran, and the second involves studying the book